Plasma synthesis of nanodiamonds in ethanol. (1st April 2019) - Nee, Chen-Hon; Lee, Ming Chuan; Poh, Hun Seng; Yap, Seong-Ling; Tou, Teck-Yong; Yap, Seong-Shan
Abstract: In this work, we examined the characteristics of the plasma formed by fs laser filamentation in ethanol that affected the nanodiamonds formation by optical emission spectroscopy. Molecular and atomic C species were detected in the plasma as the precursors to the nanodiamonds formed; above the threshold laser energy of 360 μJ. Thus, the generation of homogeneous nanodiamonds was identified to be occurred within laser energy of 360–550 μJ where atomic C, ionized C and C2 clusters coexisted. The process of fs laser filamentation is monitored with in-situ absorbance measurement of ethanol. The intensity of the absorbance peak of the sample at ∼228 nm, corresponds to intrinsic absorbance of diamond (σ→ σ* transition) was observed to increase with irradiation time. The prepared samples are characterized by using Raman spectroscopy, XPS and TEM. Nanodiamonds of <5 nm in size were produced. Photoluminescence measurements show that the sample fluoresce at ∼490 nm, when excited by 266 nm, 355 nm, 368 nm and 406 nm laser while additional photoluminescence peak is detected at 329 nm when excited by 266 nm laser.